New Granada : twenty months in the Andes / by Isaac F. Holton, M. A., professor of chemistry and natural history in middlebury college (1857)
Chapter I. Introductory -- Chapter II. Sabanilla -- Chapter III. Barranquilla -- Chapter IV. Cartagena -- Chapter V. The Magdalena Steamer -- Chapter VI. The champan -- Chapter VII. Honda and Guaduas -- Chapter VIII. Plain of Bogotá -- Chapter IX. Posada at Bogotá -- Chapter X. Bogotá -- Chapter XI. Foreigners in Bogotá -- Chapter XII. The bogotanos -- Chapter XIII. Religion and churches of Bogotá -- Chapter XIV. Churches of Bogotá -- Chapter XV. Páramo and politics -- Chapter XVI. Montserrate and the Boqueron -- Chapter VII. The prison, the hospital, the grave -- Chapter XVIII. The Valley of the Orinoco -- Chapter XIX. Congress, constitutions, institutions, and weather -- Chapter XX. The falls of Tequendama -- Chapter XXI. Balls and bulls -- Chapter XXII. The bridge of pandi -- Chapter XXIII. Ibagué -- Chapter XXIV. The back track -- Chapter XXV. Crossing the Quindio Mountains -- Chapter XXVI. A Caucan family -- Chapter XXVII. Roldanillo and law -- Chapter XXVIII. Grazier life -- Chapter XXIX. Grazier sports -- Chapter XXX. The grazier at home -- Chapter XXXI. The pastures in the forest -- Chapter XXXII. Buga and Palmira -- Chapter XXXIII. Cali and vijes -- Chapter XXXIV. Supplementary -- Appendix